Peripheral Leukocyte Apoptosis in Patients with Parkinsonism: Correlation with Clinical Characteristics and Neuroimaging Findings. (25th March 2014) - Lin, Wei-Che; Tsai, Nai-Wen; Huang, Yung-Cheng; Cheng, Kuei-Yueh; Chen, Hsiu-Ling; Li, Shau-Hsuan; Kung, Chia-Te; Su, Yu-Jih; Lin, Wei-Ming; Chen, Meng-Hsiang; Chiu, Tsui-Min; Yang, I-Hsiao; et al.
Abstract : Apoptosis of both brain neurons and peripheral blood leukocyte is believed to be an important biomarker for evaluating the functional status of Parkinson's disease (PD). However, their correlation remains unknown. A better understanding of the pathophysiology of neurodegeneration is essential for the treatment and prevention of PD. The present study demonstrated that leukocyte apoptosis is significantly higher in PD patients and is associated with central dopamine neuron loss by using Tc 99 m -TRODAT-1 SPECT. The leukocyte apoptosis and striatal dopamine transporter uptake ratios were further associated with increased severity and longer duration of disease. The interaction between brain and systemic inflammation may be responsible for the neurodegenerative disease progression.